„Mogę coś dla niej stracić, lecz nie sto tysięcy”. Helena Modrzejewska i Jan Matejko we wspomnieniach miłośnika teatru, kustosza Macieja Szukiewicza .......... 181 - Kłak-Ambrożkiewicz, Marta („Szalony, kto nie chce wyżej, jeżeli może”: Studia i materiały do badań nad życiem i twórczością Heleny Modrzejewskiej, 2025)
HELENA MODJESKA AT THE LONDON SALON IN 1880The text gives insight into the meetings between Modrzejewska and her husband Karol Chłapowski in Victorian London’s salons in 1880. Modrzejewska then fulfilled her life’s dream, achieving great theatrical success by playing in the language of Shakespeare. Invited to the first-class social salons of, among others, Hamilton Aide, Lady Mary Jeune, Lady Florence Henniker, the Chłapowskis met the most outstanding representatives of the Victorian world of politics and culture, including the Prince of Wales, the future King Edward VII, the poet laureate of Queen Victoria, Lord Alfred Tennyson, who admired Modrzejewska greatly, or Oscar Wilde, who sought her friendship. The text also talks about Lillie Langtry, an outstanding figure in the cultural and social life of London at that time, and her place in the relationship with Oscar Wilde and Modrzejewska, about Modrzejewska’s impressions from visits to London salons, about her meetings with painters, as well as about her own salon, where she hosted the most outstanding Polish singers and musicians of that time – Marcelina Sembrich-Kochańska, Józef Wieniawski, Jan and Edward Reszke – and many famous European musicians and artists.